1997
DOI: 10.1016/s0092-8674(00)80486-9
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Phosphoinositide 3-OH Kinase by the α6β4 Integrin Promotes Carcinoma Invasion

Abstract: We demonstrate that the alpha6beta4 integrin promotes carcinoma invasion through a preferential and localized targeting of phosphoinositide-3 OH kinase (PI3K) activity. Stable expression of alpha6beta4 increased carcinoma invasion in a PI3K-dependent manner, and transient expression of a constitutively active PI3K increased invasion in the absence of alpha6beta4. Ligation of alpha6beta4 stimulated significantly more PI3K activity than ligation of beta1 integrins, establishing specificity among integrins for PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

54
618
7
1

Year Published

1999
1999
2004
2004

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 590 publications
(682 citation statements)
references
References 54 publications
54
618
7
1
Order By: Relevance
“…Both mechanisms lead to an increase in intrinsic enzymatic activity (Backer et al, 1992;Rodriguez-Viciana et al, 1996) and therefore may take part of the observed PI3K deregulation. Previous reports attributed a function for PI3Ks in cell division, survival, cell dedi erentiation (Phillips et al, 1998), migration and tumour invasion (Kobayashi et al, 1999;Shaw et al, 1997). Most of these investigations did not discriminate between a and b, precluding from speci®c functions.…”
Section: Discussionmentioning
confidence: 96%
“…Both mechanisms lead to an increase in intrinsic enzymatic activity (Backer et al, 1992;Rodriguez-Viciana et al, 1996) and therefore may take part of the observed PI3K deregulation. Previous reports attributed a function for PI3Ks in cell division, survival, cell dedi erentiation (Phillips et al, 1998), migration and tumour invasion (Kobayashi et al, 1999;Shaw et al, 1997). Most of these investigations did not discriminate between a and b, precluding from speci®c functions.…”
Section: Discussionmentioning
confidence: 96%
“…Cells were co-transfected with 1 mg pCS2-(n)bGal and the cDNAs speci®ed in the ®gure legends using Lipofectamine (Gibco) according to the manufacturer's instructions. Twenty-four hours after transfection, Matrigel invasion assays were performed as described previously (Shaw et al, 1997) using 6.5 mm Transwell chambers (8 mm pore size; Costar). Matrigel was diluted in cold distilled water, added to the upper wells of the Transwell chambers (2 mg/well), and dried in a sterile hood.…”
Section: Invasion Assaysmentioning
confidence: 99%
“…These results indicate that concomitant activation of Ras and PI 3-kinase unmasks the metastatic potential of the MET oncogene. PI 3-kinase has been shown to play a role in invasion (Shaw et al, 1997). We therefore evaluated whether there was a correlation between the metastatic potential of Tpr ± Met transformed cells and the acquisition of the ability to cross a barrier of extracellular matrix.…”
Section: Enhanced Coupling Of Met To Pi 3-kinase Elicits Motility In mentioning
confidence: 99%
“…As a possible candidate we considered PI 3-kinase, which binds Y 1349 and Y 1356 at low a nity (Ponzetto et al, 1993). PI 3-kinase is a major mediator of HGF-mediated motility (Royal and Park, 1995;Kwaja et al, 1998), invasion (Keely et al, 1997;Shaw et al, 1997), and prevention from apoptosis (Kau man-Zeh et al, 1997), all events relevant to the metastatic process.…”
Section: Introductionmentioning
confidence: 99%